2015
DOI: 10.1038/srep12970
|View full text |Cite
|
Sign up to set email alerts
|

A conserved histidine in switch-II of EF-G moderates release of inorganic phosphate

Abstract: Elongation factor G (EF-G), a translational GTPase responsible for tRNA-mRNA translocation possesses a conserved histidine (H91 in Escherichia coli) at the apex of switch-II, which has been implicated in GTPase activation and GTP hydrolysis. While H91A, H91R and H91E mutants showed different degrees of defect in ribosome associated GTP hydrolysis, H91Q behaved like the WT. However, all these mutants, including H91Q, are much more defective in inorganic phosphate (Pi) release, thereby suggesting that H91 facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…In translational GTPases, switch loops I and II are involved in the GTPase activity (reviewed in Voorhees and Ramakrishnan, (2013) ). Switch loop II (aa 105–110), which carries the catalytic H108 (H92 in E. coli EF-G; ( Cunha et al, 2013 ; Holtkamp et al, 2014 ; Koripella et al, 2015 ; Salsi et al, 2014 ) is well resolved in all five structures. The histidine resides next to the backbone of G3028 of the sarcin-ricin loop and near the diphosphate of GDP ( Figure 5e ).…”
Section: Resultsmentioning
confidence: 97%
“…In translational GTPases, switch loops I and II are involved in the GTPase activity (reviewed in Voorhees and Ramakrishnan, (2013) ). Switch loop II (aa 105–110), which carries the catalytic H108 (H92 in E. coli EF-G; ( Cunha et al, 2013 ; Holtkamp et al, 2014 ; Koripella et al, 2015 ; Salsi et al, 2014 ) is well resolved in all five structures. The histidine resides next to the backbone of G3028 of the sarcin-ricin loop and near the diphosphate of GDP ( Figure 5e ).…”
Section: Resultsmentioning
confidence: 97%
“…Several independent reports suggested that substituting GTP with non-hydrolysable analogues of GTP only moderately (by 2–3 fold) slow down the rate of mRNA translocation[17, 18]. Amino acid substitutions in the G domain of EF-G that inhibited the GTPase activity of EF-G reduced the rate of mRNA/tRNA translocation by only 7 to 30 fold[12, 1921]. Furthermore, a number of antibiotics, such as viomycin or hygromycin B, strongly inhibit translocation by binding to the ribosome without impeding the binding of EF-G, GTP hydrolysis or P i release[1, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…The crude ribosome suspension was further digested with MNase at 4°C overnight. After secondary digestion, the ribosome preparation was dialyzed against HEPES-polymix buffer (59, 60). The ribosome preparation was incubated with anti-Flag M2 beads 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Initiation complex was formed by incubating 70S ribosome variants as described above (0.2 μM), [ 3 H]fMet-tRNA fMet (0.5 μM), XR7mRNA (AUG-UAA) (0.5 μM), initiation factors (0.5 μM) and GTP (1 mM) at 37°C for 15 min in HEPES-polymix buffer (59). The reactions were thereafter filtered through BA-85 nitrocellulose membranes and washed with 10ml of ice-cold HEPES-polymix buffer (pH 7.5).…”
Section: Methodsmentioning
confidence: 99%